Iconic photographs and the ebb and flow of empathic response to humanitarian disasters - Slovic, Paul; Västfjäll, Daniel; Erlandsson, Arvid; Gregory, Robin (Proceedings of the National Academy of Sciences - PNAS, 2017)
The power of visual imagery is well known, enshrined in such familiar sayings as "seeing is believing" and "a picture is worth a thousand words." Iconic photos stir our emotions and transform our perspectives about life and the world in which we live. On September 2, 2015, photographs of a young Syrian child, Aylan Kurdi, lying face-down on a Turkish beach, filled the front pages of newspapers worldwide. These images brought much-needed attention to the Syrian war that had resulted in hundreds of thousands of deaths and created millions of refugees. Here we present behavioral data demonstrating that, in this case, an iconic photo of a single child had more impact than statistical reports of hundreds of thousands of deaths. People who had been unmoved by the relentlessly rising death toll in Syria suddenly appeared to care much more after having seen Aylan's photograph; however, this newly created empathy waned rather quickly. We briefly examine the psychological processes underlying these findings, discuss some of their policy implications, and reflect on the lessons they provide about the challenges to effective intervention in the face of mass threats to human well-being.